2017
DOI: 10.1055/s-0036-1588938
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Cascade Benzyne Nucleophilic Addition/Fries Rearrangement for Entry into 2,3-Disubstituted Phenols

Abstract: Materials and Methods. Unless stated otherwise, reactions were conducted in oven-dried glassware under an atmosphere of nitrogen using anhydrous solvents. THF was obtained from an Aldrich Sureseal bottle. Tetrabutylammonium difluorotriphenylsilicate was obtained from Aldrich. The following reagents and solvents were distilled prior to use: chlorotrimethylsilane (TMSCl), trimethylsilyl trifluoromethanesulfonate (TMSOTf), tetramethylenediamine (TMEDA), and heptane. Analytical thin-layer chromatography (TLC) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Mechanistically, a Smiles-type ipso substitution on intermediate 9-128 occurs to produce Meisenheimer complex 9-129 , which in turn undergoes an extrusion of SO 2 to produce biaryls 9-127 . In 2017, a nucleophilic addition-triggered Fries rearrangement on o -silylaryl triflates 9-130 was revealed by Bronner et al, giving rise to 2,3-disubstituted phenols 9-131 in moderate to high yields (Scheme c) …”
Section: Cascade or Tandem Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanistically, a Smiles-type ipso substitution on intermediate 9-128 occurs to produce Meisenheimer complex 9-129 , which in turn undergoes an extrusion of SO 2 to produce biaryls 9-127 . In 2017, a nucleophilic addition-triggered Fries rearrangement on o -silylaryl triflates 9-130 was revealed by Bronner et al, giving rise to 2,3-disubstituted phenols 9-131 in moderate to high yields (Scheme c) …”
Section: Cascade or Tandem Reactionsmentioning
confidence: 99%
“…In 2017, a nucleophilic addition-triggered Fries rearrangement on osilylaryl triflates 9-130 was revealed by Bronner et al, giving rise to 2,3-disubstituted phenols 9-131 in moderate to high yields (Scheme 180c). 690 In 2018, Palakodety and co-workers demonstrated a basemediated cyclization of propargylic alcohols 9-132 with arynes, affording 3-benzofuranyl-2-oxindoles 9-133 along with the formation of 3-spirooxindole benzofurans 9-134 as minor products (Scheme 181). 691 692 An isocyanate intermediate 9-140 was proposed from the reaction of benzyne and acyl hydrazide 9-138, which could then react with alcohols to yield carbamates 9-139 (NuH = ROH) in modest to excellent yields.…”
Section: Cascade or Tandem Reactionsmentioning
confidence: 99%
“…12 Further relevant prior art for the proposed aryne reactivity came from Bronner and co-workers, who described an aryne nucleophilic addition−Fries rearrangement system to access Cacylated amino-phenols 15 using sulfonamides as nucleophiles (Scheme 2C). 13 We began our studies using nosylate 8a, containing an electron-deficient arene, to promote the planned Smiles− Truce rearrangement. Sulfonate 8a can be prepared in three steps from a symmetrical resorcinol starting material, using a procedure modified from that of Hosoya and co-workers (see the Supporting Information).…”
mentioning
confidence: 99%
“…An important precedent for sulfonate Smiles–Truce chemistry in the anionic regime has been reported by Quayle (Scheme B), who showed that silyl sulfonates 12 effectively undergo aryl transfer when treated with fluoride . Further relevant prior art for the proposed aryne reactivity came from Bronner and co-workers, who described an aryne nucleophilic addition–Fries rearrangement system to access C-acylated amino-phenols 15 using sulfonamides as nucleophiles (Scheme C) …”
mentioning
confidence: 99%
See 1 more Smart Citation